Experiences of Gendered Norms and Mobilizing for Rights of Women Living With Disabilities in the Post-war Context in Sri Lanka - Emmanuel, Sarala; Saroor, Shreen (Frontiers in Sociology, 2022)
This paper juxtaposes existing legal/policy frameworks, national and international, with narratives of women living with disabilities in the post-war context in Eastern Sri Lanka. These narratives highlight their lived experience and needs. The paper draws from a process of consultations among women living with disabilities and the authors, who are long standing allies of this struggle in their capacity as activists and researchers. It focuses on key aspects of myriad gendered norms that were articulated during the consultations and describes the structural discrimination that emerges from such norms, as experienced by women living with disabilities. The paper ends with some thoughts and key proposals of women living with disabilities for the future of this struggle for justice.